The Multi-configuration Dirac-Hartree-Fock Calculations for Cs VII - Wajid, Abdul; Husain, Abid; Jabeen, S.; Tauheed, A. (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2020)
Theoretical energy levels, wavelengths and transitions probabilities of six-times ionized cesium (Cs VII) are calculated using multi-configuration-Dirac-Hartree-Fock (MCDHF) method. The present calculations have been performed for the 5s\(^2\)5p, 5s\(^2\)6s, 5s\(^2\)5d, 5s5p\(^2\) configurations using the GRASP2018 package. The electron correlation effects, Breit interaction and quantum electro dynamic effects have been considered in the calculations.